CytoSorb hemoadsorption in rhabdomyolysis-induced acute kidney injury: a case report from a tertiary hospital in Bangladesh - Alam, Mohammad J.; Azad, Showkat; Hossain, M. Z. M.; Ahmed, Faisal; Chowdhury, Nasreen; Russel, Sarwar K.; Rahman, Salman; Islam, M. Shahidul; Saihum, Asif; Billah, Masum; Barua, Shantanu; Hossen, Muhammad I.; et al. (International Journal of Research in Medical Sciences, 2025)
Rhabdomyolysis is a serious clinical condition involving the breakdown of skeletal muscle, leading to the release of intracellular components into circulation. Among its complications, acute kidney injury (AKI) is the most critical, occurring in up to 50% of cases. This report presents the case of a 42-year-old male with schizophrenia and hypertension who developed rhabdomyolysis-induced AKI following a fall. He exhibited markedly elevated creatine phosphokinase (CPK) levels (360,000 u/l) and deteriorating renal function. In addition to supportive management, CytoSorb hemoadsorption was initiated. Over three sessions, CPK levels dropped to 174 u/l, and serum creatinine declined from 3.53 mg/dl to 2.16 mg/dl. This case demonstrates that CytoSorb therapy can be effective even in limited-resource settings where myoglobin assays are unavailable, offering a promising strategy for early intervention in rhabdomyolysis-induced AKI. Our experience suggests early initiation of hemoadsorption could serve as an effective adjunct in managing challenging cases where conventional therapies alone may be insufficient.